Effect Of MVVM Architecture Pattern on Android Based Application Performance - Hammamul Achdan Epiloksa; Dana Sulistyo Kusumo; Monterico Adrian (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The performance of android-based mobile applications is very important to pay attention to because performance will be related to how users will feel the experience of the application. This relates to memory usage and CPU usage on android devices when using applications. There are several ways used to improve the performance of android-based mobile applications, one of which is by applying an architecture pattern. The use of the right architecture is expected to produce good performance for android devices when running an application. Therefore, the author conducted a study on whether the application of the MVVM architecture pattern by changing the program code with the refactoring method will affect memory usage, CPU, and code execution time in Android-based applications. This is implemented using the Android Studio application and using android profiler tools to measure the performance of the application.